2016
DOI: 10.1007/s00520-016-3505-7
|View full text |Cite
|
Sign up to set email alerts
|

Physician role in physical activity for African-American males undergoing radical prostatectomy for prostate cancer

Abstract: PurposePhysical activity is recognized as a complementary therapy to improve physical and physiological functions among prostate cancer survivors. Little is known about communication between health providers and African-American prostate cancer patients, a high risk population, regarding the health benefits of regular physical activity on their prognosis and recovery. This study explores African-American prostate cancer survivors’ experiences with physical activity prescription from their physicians.MethodsThr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…There is a need to consider each individual's treatment plan when trying to engage that individual with PA . The treatment‐related barriers consistently reported by men with prostate cancer in the reviewed studies were incontinence caused by radiotherapy or radical prostatectomy, and treatment‐related fatigue, primarily relating to treatment with chemotherapy or hormone therapy, and occasionally also associated with receipt of radiotherapy or radical prostatectomy …”
Section: Qualitative Synthesis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a need to consider each individual's treatment plan when trying to engage that individual with PA . The treatment‐related barriers consistently reported by men with prostate cancer in the reviewed studies were incontinence caused by radiotherapy or radical prostatectomy, and treatment‐related fatigue, primarily relating to treatment with chemotherapy or hormone therapy, and occasionally also associated with receipt of radiotherapy or radical prostatectomy …”
Section: Qualitative Synthesis Resultsmentioning
confidence: 99%
“…Many of the included qualitative studies were of good quality, fulfilling most JBI appraisal criteria, bar that which is commonly not reported (eg, statements locating the researchers culturally/theoretically) (see Appendix S1). Methodological issues amongst the other studies and issues relating to congruity of research question, methods, and interpretation were not representing participants voices adequately, Some appraisal criteria were unfulfilled by default because of an apparent lack of detail in reporting, a common occurrence being reports not addressing the influence of the researcher on the research (and vice versa) . The consistent application of COREQ criteria for qualitative reporting may benefit this area of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men also discussed a need to seek their own information independently in order to inform decision‐making. The Internet was frequently reported as a source of valuable knowledge (Chauhan et al, 2018; Fitch et al, 2017; Hogden et al, 2019; Kassianos et al, 2015; Le et al, 2016; O'Callaghan et al, 2014; Walker et al, 2016; Williams et al, 2016) and several studies highlighted potential motivations for the use of Internet resources: Some men reported searching the Internet for information because of a perceived need to actively seek information in the process of making an informed decision, whereas others felt that information provided by their HCPs was incomplete or needed confirmation. Experiences with the use of these resources were varied.…”
Section: Resultsmentioning
confidence: 99%
“…In the UK, a wide range of HCP’s support cancer patients throughout their recovery, including GPs, oncologists, surgeons, nurses and health-care assistants. It is vital that HCPs possess a standardised knowledge of PA and how it can benefit cancer patients, as some HCPs do not prescribe PA for cancer recovery [ 24 ], which may be due to a lack of knowledge regarding the benefits of PA [ 25 ]. Additionally, programmes such as Cancer and Rehabilitation Exercise (CARE) have had variability and inconsistencies in how people have discovered their service, with some HCPs routinely promoting the service, some through patients conducting their own research and others word of mouth; this highlights the requirement for more effective and routine promotion to the CARE programme [ 23 ].…”
Section: Introductionmentioning
confidence: 99%